“Study on the efficacy of Karveeradi Tail in the management of Pama with special reference to Scabies” - GAIDHANI, KANCHAN; CHALAKH, SONALI (International Journal of Psychosocial Rehabilitation, 2020)
Scabies occurs in Individuals at all age group. Factors influencing the distribution of scabies including: age, gender, overcrowding, hygiene and season. Ancient seers categorized all skin disorders under the term “Kustha” By the sign & symptoms “Pama” can be compared with Scabies in modern science. “Study on efficacy of karveeradi Tail in the management of Pama with special reference to scabies”. In this study, 40 patients of Pama will divided into 2 groups (20 in each). In Group A (Control) – Karveeradi Tail will give for local application twice a day and Group B (Experimemtal) – Permethrin will give for local application twice a day for 7 days. Changes will be observed in subjective and objective outcomes. karveeradi Tail will be more effective than permethrin in Pama.